REVISION DE LAS TRIGONIAS DE LA ARGENTINA PARTE V: EL GRUPO DE LAS PSEUDOQUADRATAE (Ameghiniana, 2013)
In this paper, the position of Steinmannella in the pseudoquadratae trigonians is considered, with special interest on the argentinian species, which are assigned to the genus mentioned above. The paper is completed with a list of species included in Steinmannella.